Answer:
|x-15|=0
Step-by-step explanation:
Obviously.
Answer:
Step-by-step explanation:
Answer:
divide
Step-by-step explanation:
divide the first one by the second that might help
Answer:
<em>x² - 28x√x + 294x - 1372√x + 2404 </em>
Step-by-step explanation:
f(x) = + 3
g(x) = x - 7
h(x) = √x
f(g(h(x))) - ?
g(h(x)) = √x - 7
f(g(h(x))) = + 3 = ( √x - 7 )² × ( √x - 7 )² + 3 =
= (x - 14√x + 49)(x - 14√x + 49) + 3 =
= x² - 14x√x + 49x - 14x√x + 196x - 686√x + 49x - 686√x + 2401 + 3 =
= <em>x² - 28x√x + 294x - 1372√x + 2404</em>
Answer:
the time taken is 22 mins